Redox-responsive magnetic nanovectors self-assembled from amphiphilic polymer and iron oxide nanoparticles for a remotely targeted delivery of paclitaxel. Issue 30 (14th July 2021) - Ding, Xingwei; Jiang, Wenyan; Dong, Lina; Hong, Can; Luo, Zhong; Hu, Yan; Cai, Kaiyong
Abstract : A biocompatible magnetic nanoplatform based on amphiphilic polymer (HA-SS-PLA) and iron oxide nanoparticles was fabricated for the paclitaxel delivery. Abstract : To reduce the side effect of paclitaxel and enhance accumulation at the tumor site, a novel redox-responsive nanovector with excellent biocompatibility based on disulfide-linked amphiphilic polymer and magnetic nanoparticle was prepared. The system would realize PTX release due to breakage of the disulfide bond when being targeted to the tumor site by the external magnetic field. The nanovector significantly improved endocytosis and enhanced accumulation at the tumor site, with an effective inhibition of tumor cells in vitro and in vivo .